The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s10750-011-0802-5
|View full text |Cite
|
Sign up to set email alerts
|

Modern and pre-Industrial Age distributions of Cladocera in Italian and Swiss Alpine lakes

Abstract: We compared contemporary and preIndustrial Age (before 1850 AD) fossil assemblages of Cladocera in sediment cores from 25 lakes in the Italian and Swiss Alps to investigate the impact of mounting anthropogenic stresses over the last 150 years on community composition. In addition, we sought relationships between specific species and their environments by measuring nutrients, major ions, pH, alkalinity, conductivity, chlorophyll, and lake and catchment morphological features at the time of core collection for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 57 publications
1
11
1
Order By: Relevance
“…In contrast to data on zooplankton from Italian and Swiss Alpine lakes and a lake from the Niedere Tauern Alps where Daphnia has generally declined since pre‐industrial times , the present results showed a slight increase in relative Daphnia abundance towards the present. The Alpine zooplankton turnover has most likely been initiated and driven by altered limnological ranges in water temperature, ice‐cover period, stratification, and primary production.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to data on zooplankton from Italian and Swiss Alpine lakes and a lake from the Niedere Tauern Alps where Daphnia has generally declined since pre‐industrial times , the present results showed a slight increase in relative Daphnia abundance towards the present. The Alpine zooplankton turnover has most likely been initiated and driven by altered limnological ranges in water temperature, ice‐cover period, stratification, and primary production.…”
Section: Discussioncontrasting
confidence: 99%
“…However, most of the available information on the ecological preferences of Cladocera with respect to nutrients originate from studies conducted on small alpine lakes (Lotter et al 1997;Bigler et al 2006;Kamenik et al 2007;Nevalainen et al 2011) or central-eastern European lakes (Szeroczyńska 2006;Zawisza and Szeroczyńska 2007;Korponai et al 2011). Beside being less numerous, previous studies on Cladocera ecology in large and deep perialpine lakes mainly focused on individual species or responses to ecological stressors other than TP and climate, or were based on sediment cores collected before the beginning of lake restoration measures (Boucherle and Züllig 1983;Hofmann 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Cladocera remains are therefore considered to be a good proxy for environmental reconstruction (Frey 1986;Sarmaja-Korjonen 2001;Manca et al 2007;Zawisza and Szeroczyńska 2007;Nevalainen et al 2011;Alric et al 2013). They have been widely used to track historical changes in lake nutrient concentrations, either alone or in combination with other paleolimnological proxies (Jeppesen et al 2001;Davidson et al 2007), pH (Paterson 1994;Jeziorski et al 2008), and also to study historical changes in water levels (Korhola et al 2000(Korhola et al , 2005, submerged macrophyte distributions (Davidson et al 2007) and food webs (Finney et al 2000;Jeppesen et al 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…pH also influenced the distribution of cladoceran communities. The influence of pH on Cladocera has also been shown in studies in lake ecosystems, with the conclusion that low pH coincides with decreased abundances of these animals (Nilssen and Sandoy, 1990;Kurbatova, 2005;Nevalainen et al, 2011). Cladocera are components of the lowest trophic level in the classical food web and function as intermediaries between the microbial and classical food chains (Agasild et al, 2012).…”
Section: Discussionmentioning
confidence: 79%